Kānthāith̨ōt ʻongkhwāmrū ph̄ưa phatthanā sakkayaphāp khwāmkhēmkhæng læ khwāmyangȳưn kh̨ōng kānth̨ōngthīeo ch̄œng niwēt læ kānprak̨ōp thurakit dān kānth̨ōngthīeo thī phakr̄æm b̄æp hōm stē k̨ōranī sưksā Tambon Taphong læ chumchon L̄æm Rungr̄ưang, Čhangwat Ray̨ōng - Wutthichāt Sunth̨ōnsamai (Khana Manutsayasāt læ Sangkhommasāt, Mahāwitthayālai Būraphā, 2007)
Sustainable ecotourism management and home stay business development at the community-level in Rayong Province, Eastern Thailand.